Cinema of Discontent : Representations of Japan's High-Speed Growth. - Sasaki, Tomoyuki (Albany : State University of New York Press, 2022)
Uses popular films to reveal the tensions generated during Japan's postwar "economic miracle," challenging the prevailing view that it was a story of great national success.
Shōken Meets Kumashiro Tatsumi -- Jobless Men in Hokkaido -- Rausu: Rural Japan Unromanticized -- Longing for Africa -- "Stranger Intimacy" and the End of an Era -- Coda -- Notes -- Bibliography -- Online Databases -- Filmography -- Index.
Description based on publisher supplied metadata and other sources.
JSTOR
Keywords: History in motion pictures; Economics in motion pictures; Motion pictures -- Japan -- History -- 20th century; Japan -- In motion pictures; Histoire au cinéma.; Économie politique au cinéma.; Cinéma -- Japon -- Histoire -- 20e siècle.; Economics in motion pictures; History in motion pictures; Motion pictures; Japan; 1900-1999; History